An Exploration of English Students’ Attitude toward Learning English - Teuku Zulfikar; Syarifah Dahliana; Riska Amelia Sari (English Language Teaching Educational Journal, 2019)
Attitude is one of the success factors in language learning. It includes students’ feelings, beliefs, and behavior tendencies. This study is conducted using the mixed-method research  exploring English Department students’ attitude on learning English. The main focus of the study is to discover students’ belief on English, to understand students’ attitude, feeling and behavior on learning English. The data were collected through questionnaire and semi-structured interview. The participants of the reseach were fifty five students selected randomly to fill in the questionnaire. However, only six students were selected purposively to gain data more in-depth through interview. The results indicate that English department students show positive attitude in three points of cognitive aspect; the students’ reason for learning English, the students’ level of English competeent, and the students’ thinking toward learning English which they consider that English is important.  Moreover, the students have positive in four points of emotional attitude; the students’ interesting in learning English, the students’ feeling in learning English, the students’ preference in learning English, and the students’ enjoyment in learning English which the students show good feeling in learning English. Furthermore, the students have positive in three points of behavioral attitude; the students’ attention during learning English, students’ participation in the English which the students act posively during learning English. In other words, English Department students were found to have positive attitudes toward learning English.